2016
DOI: 10.4085/1062-6050-51.8.01
|View full text |Cite
|
Sign up to set email alerts
|

National Athletic Trainers' Association Position Statement: Preventing and Managing Sport-Related Dental and Oral Injuries

Abstract: Objective: To provide athletic trainers, health care professionals, and all those responsible for the care of athletes with clinical recommendations for preventing and managing sportrelated dental and oral injuries.Background: Participation in competitive sports continues to grow at both the interscholastic and intercollegiate levels. Therefore, exposure to, and the incidence of athletic-related injury, including orofacial injury, will also likely increase. At the time of this writing, the leading governing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 111 publications
(115 reference statements)
1
62
0
2
Order By: Relevance
“…Unfortunately, information about the use of mouthguards was not obtained for all patients in the present study. Wearing a mouthguard is considered effective to protect against orofacial injury and to prevent tooth fracture and avulsion. A laboratory study has suggested that a mouthguard might reduce the incidence of concussion and mandibular fracture .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, information about the use of mouthguards was not obtained for all patients in the present study. Wearing a mouthguard is considered effective to protect against orofacial injury and to prevent tooth fracture and avulsion. A laboratory study has suggested that a mouthguard might reduce the incidence of concussion and mandibular fracture .…”
Section: Discussionmentioning
confidence: 99%
“…A laboratory study has suggested that a mouthguard might reduce the incidence of concussion and mandibular fracture . However, there has been no evidence as to the efficacy of a mouthguard preventing concussion . In addition, it may not be as effective for preventing maxillofacial fractures, as a large number of fractures were observed in the zygoma and the angle and body of the mandible by direct impact.…”
Section: Discussionmentioning
confidence: 99%
“…Contact sports are those in which participants establish direct physical contact with other players or objects, resulting in greater likelihood of trauma and injuries . Dento‐alveolar injuries such as tooth avulsion, fracture, subluxation, and intrusion demonstrate a significant prevalence in recent studies . It is recommended that contact sports athletes (from football, volleyball, basketball, handball, hockey, rugby, martial arts, and others) use safety devices, such as mouthguards, to minimize impacts …”
Section: Introductionmentioning
confidence: 99%
“…2 As such, ATs play a critical role in the promotion of safe physical activity and return to participation after injury. Furthermore, the National Athletic Trainers' Association (NATA) position statements and bestpractice documents require ATs to be educated on, and assist in, preventing or otherwise managing orthopaedic injuries, [3][4][5] concussions, 6 eating disorders, 7 heat illnesses, 8 lightning injuries, 9 cardiac-related deaths, 10 diabetic episodes, 11 exertional sickling episodes, 12 early-onset osteoarthritis, 13 substance abuse, 14 disease transmission, 15 weight management, 16 and dental and oral injuries 17 in their scope of practice using evidence-based techniques. These prevention mechanisms are common practice for ATs and well within their scope of practice; however, many secondary schools that do not provide on-site AT services are left to implement these measures through other means.…”
mentioning
confidence: 99%